Diagnosing bladder outlet obstruction using the penile cuff test in men with lower urinary tract symptoms. Issue 7 (21st February 2017) - Ko, Kwang Jin; Suh, Yoon Seok; Kim, Tae Heon; Sung, Hyun Hwan; Ryu, Gyu Ha; Lee, Kyu‐Sung
Abstract : Aim: The current standard diagnostic test to evaluate bladder outlet obstruction (BOO) is pressure‐flow study (PFS). The penile cuff test (PCT) was introduced as a non‐invasive alternative to PFS to determine the isovolumetric bladder pressure and also flow rate. The aim of the study was to evaluate the diagnostic accuracy and acceptability of the PCT, compared to those of PFS, in the assessment of BOO in men. Methods: A total of 146 consecutive men with an International Prostate Symptom Score (IPSS) >12 and lower urinary tract symptoms (LUTS) for >6 months were included in this single‐institution, prospective, diagnostic study. The primary outcome was to evaluate the diagnostic accuracy of PCT. Secondary outcomes included pain severity measured on a visual analog scale (VAS), procedure time, and adverse events. In addition, the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were estimated. Results: Based on the PFS results, the sensitivity of PCT was 89.7%, the PPV 54.2%, the specificity 71.8%, and the NPV 94.9%. The mean pain VAS for the PFS and PCT were 5.04 ± 2.17 and 1.83 ± 1.98, respectively ( P < 0.0001). The mean procedure time for PCT (6.3 ± 0.6 min) was shorter than that of PFS (23.3 ± 2.2 min) ( P < 0.0001). There were no adverse events reported during PCT. Conclusions: Given its high NPV, PCT may be an efficient screening test for BOO in men. In addition, PCT is advantageous over PFS with regard to its short procedure time and acceptable tolerability.